PENCARIAN RUTE TERPENDEK PADA APLIKASI OJEK SAMPAH DENGAN MENGGUNAKAN ALGORITMA DJIKSTRA - Luluk Suryani; Ery Murniyasih (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2022)
Currently there is a transportation service at the Sorong Raya Garbage Bank. Customers for transport services are increasing day by day and this makes it difficult for drivers because they have to determine short routes every day. If the driver does not know the exact address and determines the shortest route, this will result in inefficient use of time and wasted fuel. This can also have an impact on the services provided to customers so they are not optimal because they are late or not on time. Based on the existing problems, a solution is given in the form of an application that aims to determine the shortest or closest route between each address that will be visited by the garbage collection car, this is to support the effectiveness of waste collection by providing information to the driver in the form of the shortest path to be traversed. Applications are made using the Dijkstra algorithm approach for mobile applications on the Android platform. The application is equipped with a description of the trip, estimated travel time, and alternative routes to each address. The result of the application made is that the application can implement the Djikstra algorithm which can be applied and succeeds in determining the shortest distance for the process of transporting garbage to residents' homes based on the initial address input from the driver to the pick-up destination address.